Work-Life Balance (WLB) and Job Satisfaction of Employees at PT. X Yogyakarta - Mandagi, Natania Miekemaria; Wijono, Sutarto (International Journal Labs, 2023)
The main objective of this study was to investigate the relationship between work-life balance and job satisfaction among employees at PT. X Yogyakarta, with a participant pool of 48 individuals. The research adopted a correlational quantitative approach, employing a saturated sampling technique where the entire population of eligible employees participated. To assess work-life balance, the researchers utilized the Work-Life Balance Scale (WLBS), exhibiting high internal consistency with a Cronbach alpha of 0.942. Job satisfaction was measured using the Job Satisfaction Scale, which also demonstrated excellent reliability with a Cronbach alpha of 0.972. Data collection involved the distribution of questionnaires, and the subsequent data analysis was conducted using IBM SPSS Statistics version 25, employing the Pearson Product Moment correlation test. The analysis yielded a correlation coefficient of r = 0.833, with a significance value of 0.000 (p < 0.05). This statistically significant positive correlation indicates a strong association between work-life balance and job satisfaction. In essence, the findings of this study highlight that an improved work-life balance positively influences job satisfaction among PT. X Yogyakarta employees. A higher level of work-life balance corresponds to higher job satisfaction, and vice versa. These results have important implications for the company, emphasizing the need to foster a conducive work-life balance for employees to enhance overall job satisfaction. However, further research could delve into the underlying factors that contribute to work-life balance and job satisfaction, providing a more comprehensive understanding of the intricacies of this relationship.